UnrealHaptics: Plugins for Advanced VR Interactions in Modern Game Engines - Rosskamp, Janis; Meißenhelter, Hermann; Weller, Rene; Rüdel, Marc O.; Ganser, Johannes; Zachmann, Gabriel (Frontiers in Virtual Reality, 2021)
We present UnrealHaptics, a plugin-architecture that enables advanced VR interactions such as haptics or grasping in modern game engines. The core is the combination of the integration of a state-of-the-art collision detection library with support for very fast and stable force and torque computations and a general device plugin for the communication with different input/output hardware devices such as haptic devices or Cybergloves. Our modular and lightweight architecture makes it easy for other researchers to adapt our plugins to their requirements. We prove the versatility of our plugin architecture by providing two use cases implemented in the Unreal Engine 4. In the first use case, we have tested our plugin with a haptic device in different test scenes. For the second use case, we show a virtual hand grasping an object with precise collision detection and handling multiple contacts. We have evaluated the performance in our use cases. The results show that our plugin easily meets the requirements of stable force rendering at 1 kHz for haptic rendering even in highly non-convex scenes, and it can handle the complex contact scenarios of virtual grasping.